Causes Of Firsy Molar Caries in Children Aged 7-10 Years - Diani Sulistiawati Sulistiawati; Wiworo Haryani; Eva Lydia; Cintya Dyah Ayu Saputri (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2026)
Dental caries is a multifactorial disease that remains a major dental health problem in children. The first permanent molars (M1) play an important role in chewing and occlusion but are often affected by caries due to poor oral hygiene, cariogenic food consumption, and low parental knowledge and supervision. This study aims to identify the factors that contribute to caries in the first permanent molars of children aged 7–10 years, so that it can be used as a basis for planning programs to promote and prevent dental caries in children. This study is a descriptive observational study with a cross-sectional approach. The sample consisted of 83 children aged 7–10 years. Data were obtained through clinical caries examinations and pretest–posttest questionnaires to assess children's dental health knowledge levels. Descriptive analysis was performed to examine the frequency distribution of caries and sociodemographic factors. Most respondents were male (55.4%) and aged 9 years (39.8%). The majority of fathers worked as laborers (49.4%), and 81.9% of respondents lived within 1 km of dental health facilities. The results showed an increase in dental health knowledge from 55.4% to 68.7% after health education. The highest frequency of first molar caries was found at the age of 10 years (13 children) with an average def-t index of 4.29, indicating a fairly high level of caries. First molar caries in children is influenced by socioeconomic factors, dental hygiene behavior, and the duration of tooth exposure to the oral environment. Keywords: Dental Caries; First Permanent Molars; School-Age Children; Risk Factors; Dental Health Promotion